2015
DOI: 10.1371/journal.pone.0137061
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Differences in the Relationship between Autobiographical Memory and Intertemporal Choice in Older Adults

Abstract: As the population of older adults grows, their economic choices will have increasing impact on society. Research on the effects of aging on intertemporal decisions shows inconsistent, often opposing results, indicating that yet unexplored factors might play an essential role in guiding one's choices. Recent studies suggest that episodic future thinking, which is based on the same neural network involved in episodic memory functions, leads to reductions in discounting of future rewards. As episodic memory funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…To our knowledge, this is the first study to detect an association between autobiographical memory details and temporal discounting. Previous studies found no association between overall autobiographical memory richness and discount rate (Bromberg et al, 2015;Seinstra et al, 2015). By using a composite measure of internal (episodic) details, though, these studies may have masked the finding that discounting may be related to only select types of details.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…To our knowledge, this is the first study to detect an association between autobiographical memory details and temporal discounting. Previous studies found no association between overall autobiographical memory richness and discount rate (Bromberg et al, 2015;Seinstra et al, 2015). By using a composite measure of internal (episodic) details, though, these studies may have masked the finding that discounting may be related to only select types of details.…”
Section: Discussionmentioning
confidence: 86%
“…Not only might autobiographical memory retrieval be more directly relevant to intertemporal decision-making, but the quality of autobiographical memories changes over the lifespan, becoming more schematic in healthy older adults (Levine, Svoboda, Hay, Winocur, & Moscovitch, 2002). So far, studies that have investigated the link between autobiographical memory richness and temporal discounting have yielded null results (Bromberg, Wiehler, & Peters, 2015;Seinstra, Grzymek, & Kalenscher, 2015). It is possible, however, that these studies failed to detect an association because they used a composite measure of episodic details.…”
mentioning
confidence: 99%
“…One previous correlational study conducted with healthy older adults found that global cognition was associated with temporal discounting, but episodic and semantic memory composite scores were not (Boyle et al, 2012). Another study that investigated the relationship between episodic memory ability and temporal discounting in older adults also yielded null results (Seinstra et al, 2015). These two studies, however, included only cognitively normal older adults.…”
Section: Discussionmentioning
confidence: 95%
“…These two studies, however, included only cognitively normal older adults. Furthermore, one of these studies (Seinstra et al, 2015) focused primarily on associative recognition and autobiographical memory recall, which may be less impacted by aging compared to free recall and episodic retrieval, respectively (Schroots et al, 2004;Howard et al, 2006). In the other study (Boyle et al, 2012), the episodic memory measure did not distinguish between immediate and delayed recall.…”
Section: Discussionmentioning
confidence: 99%
“…In order to assess episodic memory richness in the current study, we examined participants' autobiographical memories, which have been shown to vary in how much detail and what kinds of details they contain 32 . So far, studies that have investigated the link between autobiographical memory richness and temporal discounting have yielded null results 33,34 . It is possible, however, that these studies failed to detect an association because they used a composite measure of episodic details that conflates qualitatively different types of details.…”
mentioning
confidence: 99%